SPECIES COMPOSITION AND DISTRIBUTION OF MACROEPIBENTHOS IN THE COASTAL ZONE OF THE NORTHWESTERN TATAR STRAIT - P. A. Dulenina; N. V. Kolpakov (Известия ТИНРО, 2019)
Dredgе survey (177 stations) was conducted in the northwestern Tatar Strait (northward from 48° N) at the depths 14–82 m in summer 2018 (from July 21 to August 7). In the dredge catches, 76 species and taxa of benthic invertebrates are recorded, including 42 epibenthic species, mainly Ophiura sarsi, Evasterias echinosoma, Strongylocentrotus pallidus, Paralithodes brevipes, Cucumaria japonica, P. camtschaticus, Mizuhopecten yessoensis, and S. intermedius. The areas of their aggregations are determined. The largest area was occupied by the settlements of polyphagous S. pallidus (5100 km22 at the depths 30–60 m). Specific biomass of epibenthos is calculated, its average value within the surveyed area was 21.5 ± 2.0 g/m2. Depth ranges of the species domination are defined. The dominant species changed with latitude: in the southern part of the survey, Paralithodes camtschaticus dominated with the biomass of 5.1 ± 4.4 g/m2 in the upper 20 m layer (48–49° N), replaced at the depth of 20–30 m by P. brevipes (22.2 ± 14.2 g/m2 between 48–49° N) or C. japonica (28.2 ± 3.0 g/m2 between 49–50° N), both species changed deeper to S. pallidus (4.3 ± 1.1 g/m2); in the northern part of the survey (50–51° N), S. intermedius dominated in the upper 30 m layer with the biomass of 14.7 ± 9.5 g/m2, Mizuhopecten yessoensis (9.7 ± 6.2 g/m2 ) and Evasterias echinosoma (5.1 ± 1,0 g/m2 ) prevailed in the depth range of 30–40 m and were replaced by S. pallidus (18.0 ± 9.5 g/m2) below 50 m; in the northernmost shallow tip of the Strait, Ophiura sarsi dominated absolutely with the biomass of 13.0 ± 1.1 g/m2) in the whole depth range down to 30 m. The greatest species richness and abundance of epibenthos were observed at the depths not exceeding 40 m. Statistically significant decreasing of quantitative parameters of the epibenthos with the depth is observed because of the bottom temperature and topical diversity declination with depth. However, environmental conditions have no significant impact on latitudinal distribution of abundance, wealth and species diversity of the epifauna in the surveyed area. The grouping of epibenthos with specific species structure that could be classified as the circumlittoral one is defined in the upper shelf zone in the northernmost area with the depth < 30 m (somewhere < 40 m).